Surgery as a Potential Treatment Option for Patients With Stage III Small-Cell Lung Cancer: A Propensity Score Matching Analysis - Zhang, Chenyue; Li, Cheng; Shang, Xiaoling; Lin, Jiamao; Wang, Haiyong (Frontiers in Oncology, 2019)
It is commonly acknowledged that surgery is recommended for small cell lung cancer patients (SCLC) at stage I whereas for SCLC patients at stage III, chemotherapy and radiation therapy are considered the standard treatments. However, recent studies have indicated that a small portion of SCLC patients at advanced limited stage may benefit from surgical resection. The percentage of patients undergoing surgery for stage III SCLC is reported to account for a small portion. Therefore, in this study, we have focused on the role of surgery in SCLC patients with stage III. The Surveillance, Epidemiology, and End Results (SEER) database was used in the present study. Proper SCLC patients at stage III were selected from this database from 2004 to 2013. Propensity score matching (PSM) was applied to balance clinical bias. Overall survival (OS) was determined by Kaplan Meier analysis and compared using the log-rank test. Cox proportional hazard was employed to identify the role of surgery on OS. A total of 9606 SCLC patients at stage III were identified from the SEER database, among which 234 were subject to surgery. Compared with the non-operative group, the percentage of patients undergoing sugery had higher T1 and N0-1 stage (risen by10.7% for T1; 12.6% for N0-1) and lower T4 and N3 stage (decreased by 14.3% for T4; 12.5% for N3). Kaplan Meier analysis has found that patients subject to surgery had better OS both before and after propensity score matching (PSM). Multivariate analysis has also shown surgery was a beneficial factor for stage III SCLC patients (HR: 0.651, 95% CI (0.524-0.808), P<0.001). In conclusion, surgical resection might be associated with improved OS for selected stage III SCLC patients and may be clinically considered for these patients. Future prospective studies are warranted to confirm our findings.